Effet Anti Bactérien de L’huile essentiel de la lavande - Dourman, Ahlem (My University, 2023)
Through laboratory research conducted on aromatic plants, studies have shown that essential oils extracted from the latter have biological properties. In this way; we tried to conduct, through laboratory research, the evaluation of the antibacterial activity of essential oils extracted from dried lavender flowers. The result of extraction by steam distillation was obtained from the flowering tops, leaves and stem of the plant, and the yield was approximately 1.16%. Accordingly, as a result of studies, it has been shown that the essential oils of dried lavender flowers have weak antibacterial activity. Lavender brand, essential oils, antibac.
Keywords: Lavender; Essential Oil; Pseudomonas Aeruginosa; Acinetobacter baumannii; Proteus mirabilis; Staphylococcus Aureus; Bacillus cereus; Salmonella Enterica; Minimum Inhibitory Concentration; Minimum Bactericidal Concentration